2010
DOI: 10.1542/peds.2010-0857
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Courses of Antenatal Corticosteroids for Preterm Birth Study: 2-Year Outcomes

Abstract: Multiple courses of prenatal corticosteroid therapy, given every 14 days, did not increase or decrease the risk of death or neurologic impairment at 18 to 24 months of age, compared with a single course of prenatal corticosteroid therapy. Continued follow-up monitoring of these children is necessary to assess neurobehavioral function, school performance, and possible susceptibility to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 25 publications
1
42
0
4
Order By: Relevance
“…Our data suggest that babies exposed to repeat antenatal corticosteroids experience early catch-up in head circumference as well as weight and length. The recently published paper from Canada reports similar neurodevelopmental outcomes and growth measurements at 2 years in children exposed to either single or multiple courses of antenatal steroids 40. Whether the early and quite subtle changes in neonatal growth rates, reported from our current study, are related to later outcomes will be difficult to determine from this relatively small cohort.…”
Section: Discussionmentioning
confidence: 58%
“…Our data suggest that babies exposed to repeat antenatal corticosteroids experience early catch-up in head circumference as well as weight and length. The recently published paper from Canada reports similar neurodevelopmental outcomes and growth measurements at 2 years in children exposed to either single or multiple courses of antenatal steroids 40. Whether the early and quite subtle changes in neonatal growth rates, reported from our current study, are related to later outcomes will be difficult to determine from this relatively small cohort.…”
Section: Discussionmentioning
confidence: 58%
“…A magnetic resonance imaging study in human newborns suggested that exposure to repeated courses (Ն2 courses of 24 mg of betamethasone) to mothers at risk of preterm labor was associated with decreased cortical surface complexity (28). The results of postnatal studies of preterm human offspring exposed to repeated courses of antenatal steroids for threatened preterm labor are inconsistent, as a number of studies demonstrated no major untoward effects at 2 years of age (8,29,30), but others demonstrated a higher incidence of cerebral palsy (31), behavioral abnormalities, and/or attention issues (30,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical trials suggest that sustained exposure or repeated doses of corticosteroids are more effective in improving foetal outcomes (Abbasi et al 2000, Crowther et al 2006, Murphy et al 2008, Asztalos et al 2010. However, there is also a considerable body of evidence to suggest that multiple dosing does not carry any additional respiratory or cardiovascular benefits for the infant and is more detrimental for foetal growth and postnatal neurodevelopment, as well as adrenal function, compared with a single dose (Banks et al 1999, Spinillo et al 2004, Nair & Omar 2009, Bontis et al 2011, Murphy et al 2012.…”
Section: Implications and Concluding Remarksmentioning
confidence: 99%